Alteration and recovery of the antioxidant system induced by sub-chronic exposure to microcystin-LR in mice: Its relation to liver lipid composition - Sedan, Daniela Yazmine (2009)
The effects of MC-LR on antioxidant system in liver and kidney and its effects on hepatic lipid composition after prolonged exposure to sublethal doses of microcystins (MCs) were studied in mice. Mice were treated i.p. with 25 mg of MC-LR/kg body weight or saline solution every 2 days for a month (inflictive stage), then progression or recovery was studied for 1 and 2 months of wash-out. During the inflictive stage, MC-LR-induced oxidative damage and significant changes in liver lipids of treated mice were compared with control mice. A clear dependence of the enzyme defense system was demonstrated with reduced glutathione and a-tocopherol availabilities and a concomitant elevation in NOx production. Sub-chronic MC-LR toxicosis produced alterations in lipid components that included a decreased EFA/non-EFA, SFA/PUFA, and n-3/n-6 ratios all of which exhibited a pattern of slow recovery during the recovery periods.